Graphene oxide-supported cobalt tungstate as catalyst precursor for selective growth of single-walled carbon nanotubes. Issue 4 (18th November 2020) - Zhao, Xue; Liu, Xiyan; Yang, Feng; Liu, Qidong; Zhang, Zeyao; Li, Yan
Abstract : Graphene oxide-supported uniform cobalt tungstate nanoparticles (CoWO4 /GO) were prepared, which can be used as catalyst precursors for the diameter-controlled growth of single-walled carbon nanotubes (SWCNTs). Abstract : The preparation of uniform and well-dispersed catalysts is crucially important for the controlled growth of single-walled carbon nanotubes (SWCNTs) on substrates. We used graphene oxide (GO) as a support to prepare well-dispersed CoWO4 nanoparticles with a narrow diameter distribution. When using GO- supported CoWO4 as the catalyst precursor and performing the SWCNT growth under the optimized chemical vapor deposition conditions, we realized the diameter-controlled growth of SWCNTs with the mean size of 1.74 ± 0.18 nm. CoWO4 is a superior catalyst precursor that can be used to obtain catalyst nanoparticles with a well-controlled size. GO shows to be a feasible substrate, presenting oxygen-containing groups which act as both the binding sites to facilitate the formation of uniform nanoparticles and hydrophilic groups to ensure a good dispersibility in aqueous solution. This strategy may find wide applications in the preparation of various functional nanomaterials.